Preferensi Usaha Kecil dan Mikro di Pasar Baru Cikarang Dalam Memilih Akses Pembiayaan - Aisyah, Siti (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2014)
Preference of Micro and Small Enterprise in Pasar Baru Cikarang In Selecting Financing Access. The aim of this research is to measure the micro and small entreprise preference in Pasar Baru Cikarang in selecting of conventional or shariah financing access with using 100 responden. The Method that used in this research is binary logistic regression and descriptive analysis. There are two result of this research, first, the factor that influence the micro and small enterprise preference are the lower interest/yield, diverse product, financing plafond, and presence a guidance of business development. Second, the micro and small medium enterprise in Pasar Baru Cikarang is more preferrable access in conventional financial institution. DOI: 10.15408/aiq.v6i1.1365